Immature stages of Chewing Lice (Insecta: Phthiraptera) from Neotropical Icteridae (Aves: Passeriformes), and descriptions of three new species - Valim, Michel P. (2015)
A morphological study of six little known or undescribed species of chewing lice parasitic on cowbirds (Icteridae) is given, based on a holistic approach which includes descriptions of the pre-imaginal stages. Both sexes, the last two nymphal stages and eggs of the new species Myrsidea amblyramphidis (Amblycera: Menoponidae) are described and illustrated (type host: Amblyramphus holosericeus (Scopoli)). Also, the male with all pre-imaginal stages (including hatching organ of nymph, egg and the three nymphal stages) of Menacanthus leistidis Cicchino, 1984 from Leistes superciliaris (Bonaparte) is described for the first time and the female is redescribed; a discussion of the morphological affinities with its closest species, M. sturnellae Price, 1977 is included. Among the Ischnocera (Philopteridae s.l.), both sexes and the last pre-imaginal stages of two incompletely known species of Brueelia Kéler, 1936, B. mirabile Carriker, 1963 from Molothrus o. oryzivorus (Gmelin), and B. oxypyga (Giebel, 1874) from A. holosericeus are described. Furthermore, two new species of Brueelia, B. chopi from Gnorimopsar chopi (Vieillot), and B. paradoxa from Leistes superciliaris are described from bothsexes and their last two pre-imaginal stages, and eggs.